Outcomes of pregnancies with varying levels of nuchal translucency measurements: A population‐based retrospective study in Ontario, Canada - Bellai‐Dussault, Kara; Dougan, Shelley D.; Fell, Deshayne B.; Lavin Venegas, Carolina; Little, Julian; Meng, Lynn; Okun, Nan; Walker, Mark; Armour, Christine M.; Potter, Beth K. (Acta obstetricia et gynecologica Scandinavica, 2024)
Introduction Nuchal translucency prenatal ultrasound is widely used to screen for chromosomal abnormalities. An elevated nuchal translucency has been associated with adverse outcomes such as pregnancy loss; however, extant studies investigating these associations have had important limitations, including selection bias. This study aimed to investigate the association between nuchal translucency measurements and pregnancy outcome, specifically, a composite of pregnancy loss, termination, stillbirth, or neonatal death. Material and Methods This was a population‐based retrospective cohort study conducted with data from the prescribed perinatal registry in Ontario, Canada, Better Outcomes Registry & Network. All singleton pregnancies with an estimated date of delivery from September 1, 2016, to March 31, 2021, and multiple marker screening including a nuchal translucency were included. Pregnancies with measurements 2.0‐ < 2.5 mm, 2.5‐ < 3.0 mm, 3.0‐ < 3.5 mm, 3.5‐ < 5.0 mm, 5.0‐ < 6.5 mm, and ≥6.5 mm were compared to a reference group with measurements <2.0 mm. We used multivariable modified Poisson regression models with robust variance estimation to estimate associations between nuchal translucency measurement and pregnancy outcome, with adjustment for age at estimated date of delivery and gestational age at screening. Results There were 414 268 singleton pregnancies included in the study. The risk of pregnancy loss, termination, stillbirth, or neonatal death increased with increasing levels of nuchal translucency measurements, with an adjusted risk ratio (aRR) of 11.9 (95% confidence interval (CI) 9.9, 14.3) in the group with measurements 3.5‐ < 5.0 mm. When pregnancies with diagnosed chromosomal abnormalities were excluded, this association remained strong, with an aRR of 6.4 (95% CI 4.8, 8.5). Among pregnancies with a live birth, those with a higher nuchal translucency measurement (>5.0 mm vs. <2.0 mm) were also at increased risk of adverse perinatal outcomes such as admission to the neonatal intensive care unit and APGAR score <7. Conclusions In this population‐based study using robust methods to reduce the risk of selection bias, we found that pregnancies with increased nuchal translucency measurements are less likely to result in a live birth, even with the exclusion of chromosomal abnormalities. Pregnancies with increased nuchal translucency measurements that resulted in a live birth may also be at increased risk of adverse perinatal outcomes. Studies investigating the association between nuchal translucency measurements and pregnancy outcomes have been subject to selection bias. This study provides robust evidence of the increased risk of pregnancy loss, termination, stillbirth, or neonatal death with increasing nuchal translucency measurements.